ANALISIS STRATEGI BISNIS PADA UD. BRONTOSENO - Susilowati, Susilowati; Hapsari, Raditha Dwi Vata (Jurnal Kewirausahaan dan Inovasi, 2022)
One of the key factors for business continuity is the need to implement risk management. In this case, it is necessary to see which part is affected and plan steps to find a solution that is in accordance with the possibility of an error occurring. However, don't forget to look for new opportunities in the future. There are several strategies that must be considered and implemented by traders to survive the Covid-19 pandemic. One of them is issuing special delivery programs such as digital website facilities, marketplaces and the like to make it easier for home business customers. This research aims to identify and set the appropriate business strategy for UD. Brontoseno. This descriptive study was designed to collect data explaining the characteristics of people, events, or situations. The data was collected through documentation, library research, observations, and direct interviews with the company’s owner, employees, and customers. The methods of analysis are EFAS and IFAS, SWOT matrix, SWOT Choosing, IE (Internal-External) matrix, and QSPM. This study finds that hold and maintain is the most appropriate strategy for UD. Brontoseno and that aggressive strategy can strengthen the hold and maintain strategy.